2000
DOI: 10.1097/00007632-200009150-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Directly Applied Hypothermia in Spinal Cord Injury

Abstract: The results demonstrate that there is a statistically significant (P < 0.05) improvement in neurologic function in rats subjected to hypothermia (19 C) after insertion of a spacer that induced an ischemic spinal cord injury. This indicates that directly applied hypothermia may be beneficial in preventing injury secondary to ischemic cellular damage. The data demonstrated minimal therapeutic benefit of hypothermia (19 C) after a severe spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 28 publications
2
38
0
5
Order By: Relevance
“…In the 1960s, local profound hypothermia was produced in some patients by administering cold saline to the exposed spinal cord after laminectomy and during decompression surgeries [45,46]. These studies, along with experimental observations, provided important information regarding the ability to cool locally, and in some cases resulted in functional improvement [19,27,[47][48][49]. However, the interpretation of these studies was complicated by the fact that surgical interventions, including decompression procedures, may have led to some of the beneficial effects that were reported [46].…”
Section: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In the 1960s, local profound hypothermia was produced in some patients by administering cold saline to the exposed spinal cord after laminectomy and during decompression surgeries [45,46]. These studies, along with experimental observations, provided important information regarding the ability to cool locally, and in some cases resulted in functional improvement [19,27,[47][48][49]. However, the interpretation of these studies was complicated by the fact that surgical interventions, including decompression procedures, may have led to some of the beneficial effects that were reported [46].…”
Section: Historical Perspectivementioning
confidence: 99%
“…In studies in which the aorta is clamped for a period of time, hypothermia by epidural perfusion or other strategies of regional and systemic hypothermia have shown some promise in terms of reducing neurological deficits produced by the resulting spinal cord ischemia [65,66]. In contrast to systemic hypothermia, local cooling allows very low levels of hypothermia to be introduced without potentially initiating inherent physiological effects, such as hypotension, bradycardia, and respiratory infection that can be seen in conditions in which systemic hypothermia is used [48,52,67,68]. Nevertheless, a weakness of local cooling is that the procedure cannot be initiated until rather invasive surgical approaches are completed to allow for the application of cold fluid onto the surface of the injured spinal cord.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Since then, there have been a number of promising experimental animal studies using similar cooling methods [1,3,4,7,9]. Recently, two other successful cooling techniques have been developed, which include using an epidural cooling catheter [34,37,42] and placing a cooling saddle directly onto the spinal cord [12,14,17,18,51]. Despite the promising results in both animal and clinical experimentation, the major disadvantages of these localized cooling protocols are the invasive techniques implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies showed improved neurological outcomes, subsequent studies resulted in contrasting findings [5,6]. Malone dialdehyde (MDA) and GSH-Px levels are indicators of lipid peroxidation [7].…”
Section: Introductionmentioning
confidence: 99%